CTRPs, ?3-AR signaling, and placental fibrin deposition: molecular and histopathological aspects of preterm birth - Askin Ozek, D.; Melekoglu, R.; Akpolat, N.; Yuce, H.; Zeyveli-Celik, N.; Yasar, S.; Sandal, S. (Taylor & Francis Ltd, 2026)
It has been suggested that adipokines may modulate plasma lipid levels, and beta 3-adrenergic receptor (beta 3-AR) gene expressions may affect adipokine levels and play critical roles in lipid metabolism. This study aims to determine predictive biomarkers for preterm birth (PTB) by evaluating serum complement 1q (C1q)/tumor necrosis factor (TNF)-related protein (CTRP) levels, lipid profiles, gene expressions, and placental pathological changes in women experiencing PTB. A total of 80 pregnant women, 40 preterm and 40 term, who applied to the Department of Obstetrics and Gynecology, Faculty of Medicine, Inonu University, were included in the study. Blood and placenta samples were taken from all participants. Serum CTRP, high-density lipoprotein (HDL), low-density lipoprotein (LDL), total cholesterol (TC), and triglyceride (TG) levels were measured; beta 3-AR gene expression and detection rate of the beta 3-AR rs4994 (Trp64Arg) amplicon were evaluated. Placental tissues were examined histopathologically for perivillous/intervillous fibrin deposition and hydropic degeneration. ROC analysis was used to determine predictive biomarkers for PTB. In the PTB group, compared to the control group, beta 3-AR gene expression levels and serum CTRP3 levels were significantly decreased, while the detection rate of the Trp64Arg amplicon and serum CTRP4 levels were significantly increased. In addition, LDL levels increased significantly (p = 0.046), TC levels decreased (p = 0.045). According to ROC analysis, LDL (p = 0.039), TC (p = 0.034), CTRP3 (p = 0.019), and CTRP4 (p = 0.033) levels were determined as significant predictive biomarkers for PTB. Histopathological examination revealed increased perivillous and intervillous fibrin deposition and marked hydropic degeneration in the PTB group. Changes in CTRP levels, lipid profile disorders, and a decrease in beta 3-AR signaling pathways were found to be associated with PTB. LDL, TC, CTRP3, and CTRP4 levels can be evaluated as potential biomarkers that can be used in the early diagnosis and management of PTB.
Keywords: beta 3-adrenergic receptor; CTRP proteins; lipid metabolism; preterm birth; Trp64Arg genetic variant